Anti-inflammatory and antiresorptive effects of acyl substitution chromone derivatives in experimental model of rheumatoid arthritis - D. I. Pozdnyakov; K. N. Koryanova; K. K. Arustamyan; Ch. M. Margushev; V. S. Baskaeva; V. M. Rukovitsina; H. N. Nasrulayeva; E. A. Olokhova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2024)
Rheumatoid arthritis (RA) is a systemic inflammatory disease affecting mainly small and major joints. The development for new drugs for the treatment of RAs is constantly underway, while the purposeful synthesis of multi-targeted small molecules can be considered a promising direction for the synthesis of new anti-rheumatic drugs.The aim. To evaluate the anti-inflammatory and antiresorptive effects of acyl substituted chromone derivatives in experimental animal model for rheumatoid arthritis.Materials and methods. RА was modeled in rats by injection of a suspension of human type II collagen and a complete Freunds adjuvant (in a ratio of 1:1) under plantar aponeurosis of the hind limb of the animal. The analyzed substances under ciphers X3A7 and X3A9 at a dose of 20 mg/kg and the reference drug dexamethasone at a dose of 3 mg/kg were administered intraperitoneally for 28 days from the moment of RA modeling. On the 7th, 14th, 21st and 28th days of the experiment, the severity of the clinical manifestations of RA was determined. After 28 days, changes in the content of cytokines in the rats blood serum were assessed: tumor necrosis factor-α (TNF-α), interleukins (IL-1, IL-6, IL-10 and IL-12). Changes of myeloperoxidase activity and concentrations of matrix metalloproteinases (MMPs) of type 2 and 9 were determined in synovial tissues.Results. During the study, it was shown that the use of the tested compounds X3A7 and X3A9, as well as the reference, contributed to a decrease in the severity of clinical manifestations of RA, starting from the 14th day of the experiment. Subsequently, it was demonstrated that in animals treated with dexamethasone, the cytokine content in blood serum decreased in relation to untreated animals: TNF-α - by 57.8% (p <0.05), IL-1 - 64.1% (p <0.05), IL-6 - 59.1% (p <0.05) and IL-12 - 72.3% (p <0.05), with an increase in the level of IL-10 - by 75.4% (p <0.05). The cytokine profile of the blood serum changed similarly when the studied compounds were administered to animals. It worth be noting that against the background of the administration of dexamethasone, X3A7 and X3A9 substances, the activity of myeloperoxidase decreased by 41.7 (p <0.05), 61.7 (p <0.05) and 65.0% (p <0.05), respectively, while the concentration of MMP2 decreased by 24.0 (p <0.05), 38.5 (p <0.05) and 34.4% (p <0.05), respectively, and MMP9 - by 13.5 (p <0.05), 37.9 (p <0.05) and 35.6% (p <0.05).Conclusion. The study showed that the administration of the analyzed chromone derivatives X3A7 and X3A9 suppresses inflammatory reactions and resorptive processes in synovial tissues, which can serve as a basis for their further study as antirheumatic agents.